(3eQBI GdReGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s
(3ChdgG (B:s
(3ef bHjd SfI (B677 (3g` s
(3BNQgG (B:s
(3SfI (B688 (3g` s
(3djS Ydi GdfSNI eGjajO eQBI GdReGfs
(3EdG aj YHGQI GdNJGe hgj ef NW GdfSNI hdjSJ ONjdIs
(3hdYdg eQBI GdReGf deDda BNQ ZjQ SHW GHf GdLhRj Ch Pjd Ydi eQBg GdReGf dgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B140 s
Keywords: (3GdJGQjNs